Tumor ablation using novel photothermal NaxWO3 nanoparticles against breast cancer osteolytic bone metastasis - Jie S (Dove Medical Press, 2019)
Shuo Jie, Xiaoning Guo, Zhengxiao Ouyang Department of Orthopedics, The Second Xiangya Hospital, Central South University, Changsha, Hunan 410011, People’s Republic of ChinaCorrespondence: Xiaoning Guo; Zhengxiao OuyangDepartment of Orthopedics, The Second Xiangya Hospital, Central South University, No.139 Renmin Road, Changsha, Hunan 410011, People’s Republic of ChinaTel +86 7 318 529 5127; +86 1 354 856 0675Email guoxiaoning@csu.edu.cn; ouyangzhengxiao@csu.edu.cnBackgrounds: Profiting from the development of nanomaterials, photothermal therapy (PTT) has been discovered as efficient tumor ablation strategy for breast cancer.Materials and methods: Novel oxygen vacancy-rich tungsten bronze nanoparticles (NaxWO3) were synthesized through a simple pyrogenic decomposition process. TEM, XRD, UV-vis-NIR, photothermal conversion ability, and photothermal stability were performed. The viabilities of 293T and 4T1 cells after treating with 200 μg/mL NaxWO3 nanoparticles for 24 or 48 hrs were both above 80%, which proved the good biosafety and cytotoxicity of NaxWO3 in vitro. Two in vivo breast cancer models, namely percutaneous and intratibial 4T1 models were established and NaxWO3 (20 mg/kg) with power intensity of 1.5 W/cm2 980 nm laser photothermal treatment was used in vivo.Results: We successfully synthesized ∼150 nm NaxWO3 nanoparticles with desirable PTT effects, as evidenced by the temperature increase from 25.8°C to 41.8°C in 5 mins under the irradiation of 980 nm laser (1 mg/mL). Also, cellular compatibility of NaxWO3 nanoparticles was found upon physiologic 293T cells, in contrast with significant cytotoxicity against breast cancer 4T1 cell in vitro dose-dependently. Besides, two in vivo breast cancer models showed the decent tumor ablation ability of NaxWO3 nanoparticles, demonstrating percutaneous 4T1 tumor elimination without recurrence during 2 weeks observation as well as intratibial breast cancer inhibition with decreased bone destruction and tumor volume after NaxWO3+PTT in vivo.Conclusion: For the first time, we developed a novel oxygen vacancy-rich tungsten bronze nanoparticles (NaxWO3) through a simple pyrogenic decomposition process for PTT. Both in vitro and in vivo experiments showed the good PTT ability and tumor ablation effects of synthesized NaxWO3 nanoparticles against breast cancer osteolytic bone metastasis. Additionally, our oxygen-deficient NaxWO3 nanoparticles will expand the research horizons of PTT nanomaterials.Keywords: oxygen vacancy, NaxWO3 nanoparticles, photothermal therapy, breast cancer bone metastasis